Fungal-Mediated Degradation of Emerging Pollutants in Sewage Sludge - Rodríguez Rodríguez, Carlos E. (2012)
This chapter summarizes the novel approaches employed for the removal of emerging pollutants from sludge by means of fungal processes. The first part of the chapter introduces the potential application of fungi in bioremedia tion, which sets the background for the next chapters of the book. This includes a description of the fungal enzymatic systems usually involved in the oxidation of pollutants, as well as a brief review of the wide range of contaminants so far known to be degraded by fungi. The second half of the chapter presents the state of the art in application of fungi to remove emerging pollutants in sludge which, due to its novelty, is reduced to only a few reports performed in solid-phase and slurry reactors with Trametes versicolor, mostly under sterile conditions but with references of removal of pharmaceuticals under non-sterile conditions. Data avail able include several emerging pollutants which were grouped according to their function or activity: pharmaceutical compounds (26 drugs), brominated flame retardants (6), UV filters (7) and estrogens (3). Finally some considerations about the residual toxicity of the processes are discussed.